2020
DOI: 10.1177/0886260520967136
|View full text |Cite
|
Sign up to set email alerts
|

Distress Tolerance and Emotion Regulation as Potential Mediators Between Secondary Traumatic Stress and Maladaptive Coping

Abstract: The extant literature has illustrated that protective service workers experience negative repercussions associated with their job (including the development of secondary traumatic stress; STS) and may utilize maladaptive coping mechanisms. Developing an improved understanding of factors that might explain the relationship between STS and the utilization of maladaptive coping mechanisms is warranted. This study sought to examine emotion regulation and distress tolerance as potential mediators between STS and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 72 publications
(104 reference statements)
3
7
0
Order By: Relevance
“…Stressful events and troubles in a person's life affect their psyche and trigger the corresponding processes of receiving, interacting, and processing information, which is reflected in the person's perception, thinking, memory, and emotions. Due to the experience gained, specific mental states are developed that affect human behaviour, both in everyday life and conditions of danger (Benuto et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stressful events and troubles in a person's life affect their psyche and trigger the corresponding processes of receiving, interacting, and processing information, which is reflected in the person's perception, thinking, memory, and emotions. Due to the experience gained, specific mental states are developed that affect human behaviour, both in everyday life and conditions of danger (Benuto et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Under the influence of unfavourable factors, changes occur in the human body (on the physical, emotional, and psychological levels), where the mental state of an individual is an extremely sensitive indicator of change. Human stress resilience in the social and psychological context is considered as an individual's ability to adapt to society, maintain relationships, performance, and health, and achieve purposes (Benuto et al, 2022). Increasing a person's stress resistance or preserving it is associated with the search for resources helping to overcome the adverse effects of stressful situations (Carroll, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Emotional regulation, specifically impulse control and emotion regulation strategies are commonly studied self-regulatory processes linked to CDA perpetration (Brem, Stuart et al, 2019; Neilson et al, 2021). A risk factor closely related to emotion regulation is distress tolerance (Benuto et al, 2022), which is broadly understood as the capacity to tolerate aversive and/or emotional states (Simons & Gaher, 2005). Individuals with low distress tolerance have been shown to be more likely to use alcohol or other substances to avoid experiencing negative psychological states (Simons & Gaher, 2005), making them more susceptible to impelling factors.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, distress tolerance is considered as a promising target within a variety of psychotherapeutic approaches in the context of treatments for depression [18]. Consistent with negative reinforcement models of the development of mental disorders, the lower levels of distress tolerance of individuals, the more likely to manage their emotions using some maladaptive coping strategies to avoid negative emotional status, such as substance use problems, self-harm and suicide behaviors [19][20][21][22]. Research has shown that low levels of distress tolerance are associated with increased risk for suicide [23].…”
Section: Introductionmentioning
confidence: 99%